(untitled) (Global Journals of Research in Engineering, 2013)
Multilevel inverter is as one of the most recent and popular type of advances in power electronics. It synthesizes desired output voltage waveform from several dc sources used as input for the multilevel inverter. This paper describes a diode-clamped five-level inverter-based battery/super capacitor direct integration scheme for photovoltaic energy systems. The study is carried out for three cases. In the first case, one of the two dc-link capacitors of the inverter is replaced by a battery bank and the other by a super capacitor bank. In the second case, dc-link capacitors are replaced by two battery banks. In the third case, ordinary dc-link capacitors are replaced by two super capacitor banks. The first system is supposed to mitigate both long-term and short-term power fluctuations while the last two systems are intended for smoothening long-term and short-term power fluctuations, respectively. These topologies eliminate the need for interfacing dc#x2013;dc converters and thus considerably improve the overall system efficiency. The major issue in aforementioned systems is the unavoidable imbalance in dc-link voltages. An analysis on the effects of unbalance and a space vector modulation method, which can produce undistorted current even in the presence of such unbalances, are presented in this paper. Simulation work is done using the MATLAB software which validates the proposed method and finally THD comparison is presented for analysis